The impact of digital industry development on regional economic resilience: Evidence from China - Sui Tian; Yiran He (PLoS ONE, 2025)
With the outbreak of the global public health crisis in 2019, enhancing the resilience of regional economies has become the current focal point. Existing studies have mostly focused on the region itself, lacking exploration of regional economic resilience from the aspects of dynamics, multiple perspectives, and multidimensional integration. At the same time, the digital industry, as an emerging sector, should not only consider its impact on economic development itself, but also focus on whether it can continuously and effectively enhance the level of regional economic resilience, in order to cope with crises that may arise at any time. Therefore, through empirical methods, we conducted a detailed study of the spatial correlation and internal driving factors between the digital industry and regional economic resilience, aiming to build a more valuable theoretical framework based on existing research findings and explore a regional resilience development strategy centered around the digital industry. This paper, combining conclusions and methods from existing literature, attempts to expand the definition of regional economic resilience, evaluation index system, and the relationship with the digital industry from the perspective of evolutionary economic geography. This article empirically examines data from 30 provinces in China from 2014 to 2022 (excluding Tibet, Hong Kong, Macau, and Taiwan due to lack of data). Firstly, this paper employs a two-way fixed effects model to examine the direct relationship between digital industry development and regional economic resilience. The research results indicate that the development of the digital industry can effectively enhance regional economic resilience. Secondly, the role of spatial location, as an important aspect of evolutionary economic geography, is also considered in this paper. The spatial Durbin model is used to discover spatial spillover effects of digital industry development on regional economic resilience under different spatial location relationships. Finally, this paper considers environmental regulations as a threshold variable to study the impact of the digital industry on regional economic resilience under different levels of environmental regulation. The results indicate that when the degree of environmental regulation is less than 0.0011, the digital industry can more effectively empower the enhancement of regional economic resilience levels. In conclusion, this paper finds that while emphasizing the role of the digital industry in the resilient development of regional economies, it is also essential to promote regional cooperation for mutual benefit and win-win results. This will accelerate the transformation of digital enterprises, optimize industrial structures, and achieve green development.